Petrology and Geochemical Comparation of Pumice and Scoria Rocks of Slamet Volcano, Central Java - Yogi Adi Prasetya; Atsushi Toramaru (Journal of Applied Sciences, Management and Engineering Technology, 2022)
Slamet Volcano is one of Indonesia Quaternary Stratovolcanoes in Central Java Province. Slamet volcano is divided into two parts, Old Slamet in the western part and Young Slamet. The author examined a comparation data of pyroclastic rock of Slamet Volcano, the pyroclastic rocks are pumice from Old Slamet, the scoria fall, and scoria cones are from Young Slamet. They have different geochemical and petrology features, pumice rock has higher SiO2 from 60 to 64 wt.%, scoria fall has SiO2 49.81 to 50.56 wt. %, and scoria cone has SiO2 49.26 wt. %. Petrographic observation showed that pumice is vesicular and contains of phenocryst pyroxene, plagioclase and biotite, scoria fall, and scoria cones have similar petrographic characteristic they have phenocryst of plagioclase, olivine, and pyroxene with hyalopilitic texture. The contrast of major element combined with petrographic features suggest that pyroclastic rock in Slamet Volcano formed by different magma and the magma has differentiation process of Slamet magma is generally caused by magma mixing.